Military treatment of splenic injury in the era of non-operative management. Issue 2 (22nd March 2013) - Mossadegh, Somayyeh; Midwinter, M; Sapsford, W; Tai, N
Abstract : Objectives: Management of blunt splenic injury (BSI) in battlefield casualties is controversial. Splenectomy is the traditional treatment, as setting the conditions for selective non-operative management (SNOM) is difficult in the operational environment. On mature operations, it may be feasible to adopt a more conservative approach and manage the patient according to civilian protocols. The aim of this study was to document the contemporary practice of deployed military surgeons when dealing with BSI and to compare this against a matched cohort of civilian BSI patients. Method: The Joint Theatre Trauma Registry held at the Royal Centre for Defence Medicine, Birmingham, was thoroughly examined to yield patients with BSI. The study encompassed a 55-month period ending September 2009. Data abstracted included patient demographics, injury epidemiology, grade of splenic injury, treatment and outcome. These data were compared with a registry database from a UK civilian major trauma centre. Result: Of 1516 military trauma patients, 16 (1%) had a splenic injury, of which five were excluded either because of fatalities due to overwhelming injury or penetrating trauma. The remaining 11 had a blunt component. Median (IQR) injury severity score (ISS) was 17 (15–21). Nine underwent a splenectomy with median (IQR) ISS of 17 (12–18). Of this group, organ injury grades were documented in 10 patients (four Grade V injuries, three Grade IV and three Grade II). All patients survived surgery. There were no complications in survivors as a result of splenic conservation in the military group. Data from the civilian major trauma centre database showed 160 (2%) patients sustained a splenic injury, of which 131 (82%) had a blunt mechanism, 43/160 (27%) and 9/160 (6%) patients underwent splenectomy and angio-embolisation, respectively. Conclusions: Patients with BSI, an uncommon finding in combat casualties, are occasionally selected for conservative management, contrary to previous military surgical paradigms but in keeping with the civilian shift to SNOM. Guidelines to clarify the place of SNOM are required to assist surgical decision making on deployed operations.